Mission Spirituality and Authentic Discipleship. - Ma, Wonsuk (Edinburgh Centenary., 2013)
This book argues for the primacy of spirituality in the practice of mission. Since God is the primary agent of mission and God works through the power of the Holy Spirit, it is through openness to the Spirit that mission finds its true character and has its authentic impact. This is demonstrated today particularly by movements of Christian faith in the global south which carry the good news to the heart of communities in every part of the world. Originating in the Edinburgh 2010 mission study project, the essays assembled in this volume show that today there is a renewal of the missionary impetus of the churches which is marked by its spiritual character. Here fresh motivation for mission is being found, moving people of faith to share the good news of Jesus Christ both within their own communities and by crossing frontiers to take the message to new contexts.